SONOGRAPHIC BIOPHYSICAL PROFILE IN DETECTION OF FOETAL HYPOXIA IN 100 CASES OF SUSPECTED HIGH RISK PREGNANCY - Ullah, Nadeem; Usman, Muhammad; Khan, Abdur Rehman (Journal of Ayub Medical College Abbottabad, 2010)
Background: The foetus has become increasingly accessible and visible as a patient over the last two decades. Ultrasound imaging has broadened the scope of foetal assessment. Dynamic real time B-Mode ultrasound is used to monitor cluster of biophysical variables, both dynamic and static collectively termed as biophysical profile. The purpose of this study was to determine the effect of sonographic biophysical profile score on perinatal outcome in terms of mortality and morbidity. Methods: This descriptive study was carried on 100 randomly selected high risk pregnant patients in Radiology Department PGMI, Government Lady Reading Hospital, Peshawar from December 2007 to June 2008. Manning biophysical profile including non-stress was employed for foetal screening, using Toshiba ultrasound machine model Nemio SSA-550A and 7.5 MHZ probe. Results: Out of 100 cases 79 (79%) had a normal biophysical profile in the last scan of 10/10 and had a normal perinatal outcome with 5 minutes Apgar score >7/10. In 13 (13%) cases Apgar score at 5 minute was < 7/10 and babies were shifted to nursery. There were 2 (2%) false positive cases that showed abnormal biophysical profile scores of 6/10 but babies were born with an Apgar score of 8/10 at 5 minutes. There were 2 (2%) neonatal deaths in this study group. The sensitivity of biophysical profile was 79.1%, specificity 92.9%. Predictive value for a positive test was 98.55%; predictive value for a negative test was 41.93%. Conclusion: Biophysical profile is highly accurate and reliable test of diagnosing foetal hypoxia. Keywords: Foetal biophysical profile, High risk pregnancy, Perinatal outcome